Cdk6 blocks myeloid differentiation by interfering with Runx1 DNA binding and Runx1-C/EBPalpha interaction. - Fujimoto, T; Anderson, K; Jacobsen, SE; Nishikawa, S; Nerlov, C (2007)
Interactions between the cell cycle machinery and transcription factors play a central role in coordinating terminal differentiation and proliferation arrest. We here show that cyclin-dependent kinase 6 (Cdk6) is specifically expressed in proliferating hematopoietic progenitor cells, and that Cdk6 inhibits transcriptional activation by Runx1, but not C/EBPalpha or PU.1. Cdk6 inhibits Runx1 activity by binding to the runt domain of Runx1, interfering with Runx1 DNA binding and Runx1-C/EBPalpha interaction. Cdk6 expression increased myeloid progenitor proliferation, and inhibited myeloid lineage-specific gene expression and terminal differentiation in vitro and in vivo. These effects of Cdk6 did not require Cdk6 kinase activity. Cdk6-mediated inhibition of granulocytic differentiation could be reversed by excess Runx1, consistent with Runx1 being the major target for Cdk6. We propose that Cdk6 downregulation in myeloid progenitors releases Runx1 from Cdk6 inhibition, thereby allowing terminal differentiation. Since Runx transcription factors play central roles in hematopoietic, neuronal and osteogenic lineages, this novel, noncanonical Cdk6 function may control terminal differentiation in multiple tissues and cell types.